Multifunctional biomimetic hydrogel systems to boost the immunomodulatory potential of mesenchymal stromal cells. (October 2020) - Gonzalez-Pujana, Ainhoa; Vining, Kyle H.; Zhang, David K.Y.; Santos-Vizcaino, Edorta; Igartua, Manoli; Hernandez, Rosa Maria; Mooney, David J.
Abstract: Mesenchymal stromal cells (MSCs) hold great therapeutic potential, in part because of their immunomodulatory properties. However, these properties can be transient and depend on multiple factors. Here, we developed a multifunctional hydrogel system to synergistically enhance the immunomodulatory properties of MSCs, using a combination of sustained inflammatory licensing and three-dimensional (3D) encapsulation in hydrogels with tunable mechanical properties. The immunomodulatory extracellular matrix hydrogels (iECM) consist of an interpenetrating network of click functionalized-alginate and fibrillar collagen, in which interferon γ (IFN-γ) loaded heparin-coated beads are incorporated. The 3D microenvironment significantly enhanced the expression of a wide panel of pivotal immunomodulatory genes in bone marrow-derived primary human MSCs (hMSCs), compared to two-dimensional (2D) tissue culture. Moreover, the inclusion of IFN-γ loaded heparin-coated beads prolonged the expression of key regulatory genes upregulated upon licensing, including indoleamine 2, 3-dioxygenase 1 ( IDO 1) and galectin-9 ( GAL9) . At a protein level, iECM hydrogels enhanced the secretion of the licensing responsive factor Gal-9 by hMSCs. Its presence in hydrogel conditioned media confirmed the correct release and diffusion of the factors secreted by hMSCs from the system. Furthermore, co-culture of iECM-encapsulated hMSCs and activated human T cells resulted in suppressed proliferation, demonstrating direct regulation on immune cells. These data highlight the potential of iECM hydrogels to enhance the immunomodulatory properties of hMSCs in cell therapies. Graphical abstract: Image 1